(untitled) (Journal of Fatima Jinnah Medical University, 2019)
Background: Transabdominal ultrasound is readily available, cost effective and first line investigation for pelvic pathologies in girls of adolescent age group. It avoids unnecessary radiation exposure due to CT imaging. Ovarian dermoid cyst is common benign pathology among young girls. In present study we have determined the transabdominal ultrasound sensitivity, specificity and diagnostic accuracy for diagnosis of dermoid cyst of ovary taking histopathology as gold standard. Patients and methods: This cross-sectional study was conducted at Diagnostic Radiology Department, Sir Ganga Ram Hospital Lahore from 25th Nov 2014 to 24th May 2015. In this study 150 patients (age 6 to 25 years) were included with clinical suspicion of ovarian mass or lower abdominal pain. Transabdominal sonography was carried out and diagnosis i.e. presence of ovarian dermoid cyst or its absence were recorded. All the patients (with a lower abdominal/pelvic mass) underwent surgery either by laparoscopy or laparotomy (therapeutic/diagnostic) and postoperative specimen were sent for histopathology. The results of transabdominal sonogram and histopathology were compared taking histopathology as gold standard. Results: After comparison of results of transabdominal sonography with histopathology the sensitivity, specificity of transabdominal ultrasound were 92.7%, 87.5% and diagnostic accuracy was 91.3%. Negative and positive predictive values were 95.3% and 81.3% respectively. Conclusion: The transabdominal ultrasound is very accurate and sensitive modality for diagnosis of ovarian dermoid cyst. Moreover transabdominal ultrasound is easily available first line imaging technique for the diagnosis of this common pelvic lesion (dermoid cyst) among adolescent and young girls.